Bullfighting rite and tragedy through the stagements of Coronada y el toro, by Francisco Nieva (XXI Century. Spanish Literature and Culture, 2024)
This paper analyzes Coronada y el toro, by Francisco Nieva, as an example of Dionysian tragedy, according to Nietzsche's theoretical proposal. In this theatre piece the bullfighting ritual is presented as the guiding thread of a latent Dionysianism that can only be consummated in scenic materiality. Therefore, we explore how the dramaturgical aesthetics of the two main productions of the work —the one directed by Nieva himself in 1982 and the more recent one by Rakel Camacho in 2023— interact with these elements of the work.
Keywords: Coronada y el toro; dionysian tragedy; tauric rite; Francisco Nieva; Rakel Camacho